The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/brs.0000000000004287
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Regret Among Older Adults Undergoing Corrective Surgery for Adult Spinal Deformity: A Single Institutional Study

Abstract: While surgery for ASD is beneficial and results in functional improvement, in over 20% of older adults outcomes from surgery are less desirable. 80% of patients agreed that having surgery was the right decision for them, 77% would make the same choice in future, and 21% regretted their choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The authors likewise reported that decisional regret is a relatively common finding among surgical patients, citing a range of 2% to 40%. 5,13,14 However, most of these studies constituted surgeries for oncologic pathology. We herein illustrate that postoperative decisional regret among patients undergoing spine surgery for degenerative conditions is at the lower end of this spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors likewise reported that decisional regret is a relatively common finding among surgical patients, citing a range of 2% to 40%. 5,13,14 However, most of these studies constituted surgeries for oncologic pathology. We herein illustrate that postoperative decisional regret among patients undergoing spine surgery for degenerative conditions is at the lower end of this spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also concluded that patients with higher regret exhibited a greater prevalence of depression and anxiety. 5 To the best of our knowledge, no studies have evaluated decisional regret in patients with degenerative spine conditions. Thus, the present study aimed to explore how patients retrospectively viewed their decision to pursue spine surgery for degenerative lumbar pathology and evaluate factors correlated with decisional regret among this patient population.…”
mentioning
confidence: 99%
“…Although these conferences require structured collaboration between multiple care providers, their applicability and utility are within reach in many institutions and have been reproduced in the literature. 20 Recent evidence has shown that 20% of patients who undergo spinal deformity surgery may regret their decision, 21 perhaps secondary to unrealistic expectations of surgery and its outcomes. 22 Sikora et al 22 demonstrated that only 17% of patients presenting for spine deformity surgery in a high-volume institution had an absence of a psychiatric comorbidity and expectations of surgery that were felt to be "realistic" by the surgical team based on typical outcomes presented to patients during a shared decision-making process.…”
Section: Personalized Preoperative Assessmentmentioning
confidence: 99%
“…This study from Houston (Texas, USA) investigated whether patients who underwent such surgery were satisfied with their outcomes, and whether they would make the same decision to proceed with surgery again. 2 This is a useful study to help inform decisions in a very difficult area. For the purposes of this study, 155 patients, with a mean age of 69.5 years, underwent spinal surgery in a large quaternary centre.…”
Section: Decisional Regret Among Older Adults Undergoing Corrective S...mentioning
confidence: 99%